White Utopias: The Religious Exoticism of Transformational Festivals - Lucia, Amanda J. (University of California Press, 2020)
Frontmatter -- Contents -- List of Illustrations -- Acknowledgments -- Author Note -- Introduction -- 1. Romanticizing the Premodern -- Interlude -- 2. Anxieties over Authenticity -- Interlude -- 3. Deconstructing the Self -- Interlude -- 4. Wonder, Awe, and Peak Experiences -- Interlude -- 5. The Cathartic Freedom of Transformational Festivals -- Conclusion -- Appendix 1: Instagram Data for Public Figures Cited -- Appendix 2: Methodology -- Notes -- References -- Index